Development and commissioning of test device for bearings used in wind turbine gearbox high speed shaft - Paattakainen, Oula (2019)
Wind energy market pressure towards lower levelized cost of energy has led to size optimizations for wind turbine gearboxes which are one of the most important turbine subcomponents in converting the slow rotor speed to high speeds suitable for the electricity grid connected generator. Gearbox size optimization decreases material costs but in turn introduces challenges for example for gearbox lubrication solutions. The so called high speed shaft (HSS) and its bearings are often the most critical components for lubrication. Because the HSS is connected to the generator its rotational speed is the highest and therefore it usually also experiences the highest temperatures. Based on these considerations a component level test device for high speed shaft bearings had been designed. Process variable measurement system, automation control logic and simulation model were developed for the test device in the practical part of this thesis. Practical work also included the commissioning of test device and execution of reference tests. Main goal of the measurements was to study the lubrication oil's temperature change from bearing inlet to outlet. It was observed that previously used estimation of increase of 10 °C is applicable only for part of the tested bearings. Analysis of test results was limited by the notion that the measured torque losses for the test device were significantly higher than expected based on theoretical values. However, the practical implementation of measurement and control system was deemed successful. Increased torque losses were hypothesized to be due to load independent oil drag losses and therefore future test with HSS bearing tester should focus on decreasing the drag losses closer to a level corresponding to theory.